Antibacterial Effectiveness Test of Combination Ethanol Extract of Rosella Flowers (Hibiscus Sabdariffa) and Green Betel Leaves (Piper betle L) on Growth Escherichia coli - Pradivtha, I Wayan Anantha; Wanadiatri, Halia; Rusmiatik, Rusmiatik; Lestari, Novianti Anggie (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Infections from bacteria like Escherichia coli continue to be a major health issue, especially because of the rising rates of antibiotic resistance. This situation emphasizes the necessity for creating different antibacterial solutions that come from natural sources. The Roselle flower (Hibiscus sabdariffa L.) and the green betel leaf (Piper betle L.) are recognized for having several secondary compounds that may have antibacterial properties. This study aimed to determine the antibacterial effectiveness of a combination of ethanol extracts of roselle flower and green betel leaf against the growth of Escherichia coli. This study was an experimental laboratory study using a post-test only control group design. Ethanol extractions from the roselle flower and green betel leaf were assessed separately at a concentration of 100% and together at a ratio of 50%:50%. The antibacterial properties were examined using the disk diffusion technique. Ciprofloxacin was utilized as a positive control, and 10% Dimethyl Sulfoxide acted as a negative control. The findings indicated that the 100% ethanol extract of the roselle flower yielded an average inhibition zone diameter of 19.6 mm, whereas the 100% ethanol extract of the green betel leaf resulted in an average inhibition zone diameter of 29.4 mm. The combined extract at a 50%:50% ratio showed an average inhibition zone diameter of 25.2 mm. Thus, it can be concluded that the mixture of ethanol extracts from the roselle flower and green betel leaf demonstrates significant antibacterial effects against Escherichia coli, although it remains less effective than the green betel leaf extract alone.